Effect of axial magnetic field tapering on whistler-pumped FEL amplifier in collective Raman regime operation - Gopal, Ram; Kumar Jain, Pradip; Kumar Jain, Pradip (International Journal of Engineering and Technology, 2018)
The dispersion relation of the FEL Amplifiers is sensitive to the linear tapered strong axial magnetic fields, electron cyclotron frequency and plasma frequency of electrons. For the synchronism of the pumped frequency, it should be closed to electron cyclotron frequency which is resonantly enhanced the wiggler wave number that produces the amplifier radiation for higher frequency from sub millimeter wave to optical ranges. The guiding of radiation signal into the waveguide and charge neutralization phenomenon, the beam density should be greater than the background plasma density with tapered strong axial magnetic field. It is quite considerable that radiation signal slowed down at much higher background plasma density comparable to the density of beams and enhanced the instability growth rate also. In Raman Regime operation, the growth rate decreases as increases with operation frequency of the amplifier, however, the growth rate is larger in this regime. It is noted that as increases with background plasma density, the beat wave frequency of the Ponderomotive waves is increases thus the mechanism of background plasma density can serve for tenability of the higher frequencies. The tapering of the strong guided magnetic field is a crucial role for enhancing the efficiency of the net transfer energy as well as reduction of interaction region along the axis. It is observed that, an efficiency of the transfer energy enhanced by while the reduction along the interaction region of about with the variation of tapering in a strong axial guided magnetic fields.Â Â